The use of a two-frequency eddy current method for measuring the electrically conductive wall thickness under significant variations in the test parameter and the lift-off - A.E. Goldshteyn; Kh.Kh. Abakumov (Қарағанды университетінің хабаршысы. Физика сериясы, 2022)
The paper addresses the problem of eddy current testing of the wall thickness of light-alloy drill pipes under significant variations in both the test and the influence parameter of the test object – the lift-off between the eddy current probe and the test object surface. The performance of the two-frequency eddy current method is shown through the use of the signal of the surface eddy current probe of the added high-frequency voltage amplitude as an informative parameter to measure the lift-off and the phase of the added low-frequency voltage. Experimentally obtained dependences of the informative parameters on test and influence parameters are presented. The phase and amplitude-phase multi-parameter methods used to suppress the effect of stray parameters in eddy current testing are analyzed; the effectiveness of their application under significant variations in test and other influence parameters of the test object is shown to be limited. The effectiveness of nonlinear functions for the inverse transformation of the informative parameter into the test parameter to suppress the lift-off effect on test results is estimated. Criteria of choice for informative parameters of the eddy current probe signal are considered. The measurement error caused by the approximation error of the nonlinear functions of the inverse transformation of the informative parameters into the test parameter within the variation ranges of the test and influence parameters is estimated